EXPERIMENTAL INVESTIGATIONS OF THE PROCESS OF ROLLING STRIPS OF VARIABLE THICKNESS WITH A LOCAL BEND - V. A. Korol'; L. A. Isaevich; D. M. Ivanickij; A. I. Gordienko (Литьë и металлургия)
The results of computer simulation and experimental investigations of the rolling process of strip blanks on the profiled mandrel using two processing schemes